The repository of agricultural policies in Cameroon and its social and institutional construction (from 2006 to 2015): a constructivist and institutionalist analysis of public policy - (:unkn) unknown (My University, 2021)
After more than a century (1884 -2016) of promoting a development supported by the agricultural sector as lever for action by majority of Sub-Saharan African states, our research highlights the imperceptibility or ineffectiveness of this reality, especially for the specific case of Cameroon by analyzing the relationship between agricultural governance and development through an appreciative description of the agricultural policies design and implementation. Through an institutionalist and constructivist public policy analysisapproach oriented towards decision-making support, (for utilitarian ends of its results), this research tries to understand and make understand, the phase shifts between this central positioning of the agricultural sector (in lever of the development) and its performances which remain globally below its real potentialities. Its temporal and conjunctural demarcation favors the reference period 2006-2015 which best highlights the contrast between the hopes aroused and drained by the achievement of the Completion Point of the HIPC Initiative in 2006 for Cameroon and its sub-region (the Central Africa), and the unceasing performance at half-mast of the agricultural sector both in terms of food self-sufficiency and poverty reduction.
Keywords: African Research